Adventitial macrophage accumulation impairs perivascular nerve function in mesenteric arteries with inflammatory bowel disease - Grunz, Elizabeth A.; Jones, Benjamin W.; Lateef, Olubodun Michael; Sen, Sidharth; Wilkinson, Katie; Joshi, Trupti; Boerman, Erika M. (Frontiers in Physiology, 2023)
Introduction: Inflammatory bowel disease (IBD) involves aberrant immune responses and is associated with both cardiovascular disease risk and altered intestinal blood flow. However, little is known about how IBD affects regulation of perivascular nerves that mediate blood flow. Previous work found perivascular nerve function is impaired in mesenteric arteries with IBD. The purpose of this study was to determine the mechanism of impaired perivascular nerve function. Methods: RNA sequencing was performed on mesenteric arteries from IL10-/- mice treated with H.hepaticus to induce disease (IBD) or left non-gavaged (Control). For all other studies, Control and IBD mice received either saline or clodronate liposome injections to study the effect of macrophage depletion. Perivascular nerve function was assessed using pressure myography and electrical field stimulation. Fluorescent immunolabeling was used to label leukocyte populations and perivascular nerves. Results: IBD was associated with increased in macrophage-associated gene expression, and immunolabeling showed accumulation of adventitial macrophages. Clodronate liposome injection eliminated adventitial macrophages, which reversed significant attenuation of sensory vasodilation, sympathetic vasoconstriction and sensory inhibition of sympathetic constriction in IBD. Acetylcholine-mediated dilation was impaired in IBD and restored after macrophage depletion, but sensory dilation remained nitric oxide independent regardless of disease and/or macrophage presence. Conclusion: Altered neuro-immune signaling between macrophages and perivascular nerves in the arterial adventitia contributes to impaired vasodilation, particularly via dilatory sensory nerves. Targeting the adventitial macrophage population may help preserve intestinal blood flow in IBD patients.